Verification of a Torsional Behaviour Prediction Model for Reinforced Recycled Aggregate Concrete Beams - Aqeel H. Chkheiwer; Mazin A. Ahmed; Zahir M. N. Hassan (Journal of Engineering)
This study shows the torsional conduct of aggregate streaming beams of reinforced concrete recycling. Pure torsion was perceived for 15 reinforced concrete beams containing recycled concrete aggregates. The beams were grouped into five lengths and cross-sectional groups. The study’s principal parameters were the various percentages of longitudinal steel reinforcement and the proportions of recycled aggregates. The beams were purely twisted until failure and investigated for torsional and crack behaviour. The findings show that the beams with maximum steel enhancement and standard aggregate exhibited maximum cracking power and ultimate torsional strength. Recycled aggregates increased the presence of splitting and the ultimate strength, and the effects of steel strengthening in recycled beams were apparent. In a second analysis, the whole torsional reaction of the beams was analytically predicted. A soft truss model was used and matched with test results for standard beams. A strong compromise was generally reached.